Digital Marketing Study: The Role Of Country Of Origin, Product Quality And Celebrity Endorser On Purchase Decisions - Najmudin, Mohamad; Shalsyabila, Minda; Ilyas, Gunawan Bata; Helmi, Sulaiman (International Journal of Artificial Intelligence Research, 2022)
This study This study aims to determine the effect of country of origin, product quality, and celebrity endorser on purchasing decisions of Nature Republic Aloe Vera Soothing Gel in Yogyakarta. Samples were taken as many as 112 respondents using purposive sampling technique. The population in this study were all users of Nature Republic Aloe Vera Soothing Gel products in Yogyakarta. Multiple linear regression analysis was used to test the hypothesis of this study. The results of this study indicate that country of origin and product quality have a positive effect on purchasing decisions, while celebrity endorsers have no effect on purchasing decisions.